1992
DOI: 10.1002/j.1460-2075.1992.tb05493.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation of CDK2 activity by phosphorylation of Thr160 and Tyr15.

Abstract: We have examined the role of phosphorylation in the regulation of human cyclin‐dependent kinase‐2 (CDK2), a protein closely related to the cell cycle regulatory kinase CDC2. We find that CDK2 from HeLa cells contains three major tryptic phosphopeptides. Analysis of site‐directed mutant proteins, expressed by transient transfection of COS cells, demonstrates that the two major phosphorylation sites are Tyr15 (Y15) and Thr160 (T160). Additional phosphorylation probably occurs on Thr14 (T14). Replacement of T160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
460
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(498 citation statements)
references
References 60 publications
34
460
2
2
Order By: Relevance
“…The slowing of proliferation appeared to be beneficial for cell health since the induction of apoptosis was completely blocked and the percentage of G o /G 1 -arrested cells was reduced virtually to control under these conditions. That IL-4 maintains a net proliferative advantage is shown by the data presented in Figure 1 and is supported by those presented in Figure 3 where IL-4 maintained CDK2 activation (pCDK2, [35]), suppressed p27 Kip1 protein expression, and prevented the down-regulation of c-Myc. In a recent profile of genes using the GS320 system TM (Capital Genomix, Gaithersburg, MD), we observed that anti-IgM treatment down-regulated CDK2 mRNA in both ECH408 and WEHI-231 cells (both undergo apoptosis in response to anti-IgM treatment).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The slowing of proliferation appeared to be beneficial for cell health since the induction of apoptosis was completely blocked and the percentage of G o /G 1 -arrested cells was reduced virtually to control under these conditions. That IL-4 maintains a net proliferative advantage is shown by the data presented in Figure 1 and is supported by those presented in Figure 3 where IL-4 maintained CDK2 activation (pCDK2, [35]), suppressed p27 Kip1 protein expression, and prevented the down-regulation of c-Myc. In a recent profile of genes using the GS320 system TM (Capital Genomix, Gaithersburg, MD), we observed that anti-IgM treatment down-regulated CDK2 mRNA in both ECH408 and WEHI-231 cells (both undergo apoptosis in response to anti-IgM treatment).…”
Section: Discussionsupporting
confidence: 60%
“…Previous results from the Scott lab demonstrated that treatment of CH31 with anti-IgM results in the loss of c-myc [30] and inactivation of CDK2 [19], an enzyme that promotes cell cycle progression and suppresses accumulation of the cyclin-dependent kinase inhibitor p27 Kip1 through phosphorylation and proteasomal targeting [34]. Phosphorylation of CDK2 on Threonine 160 (pCDK2) is required for CDK activity and, therefore, the measurement of T 160 phosphorylation is an excellent indicator of its activation [35]. Consistent with previous results, we confirmed that treatment of CH31 cells with anti-IgM resulted in a loss of c-myc expression, loss of pCDK2 and a rise in expression of the CDK inhibitor p27 Kip1 ( Figure 3).…”
Section: Effect Of Il-4 On Anti-igm-induced Growth Arrest and Apoptosismentioning
confidence: 99%
“…Our transgenic models reveal, for the ®rst time, that cdk2b, but not cdk2a, occurs as the faster-migrating phosphorylated form (Gu et al, 1992;Planas-Silva et al, 1997) in a primary tumor tissue. Little is known about functions of cdk2b.…”
Section: Discussionmentioning
confidence: 59%
“…In mouse, rat and hamster, the cdk2b is an alternate RNA splicing form of cdk2a, the classic cdk2, with an insert of 48 amino acids between amino acids 196 and 197 of cdk2a. The cdk2a isoform occurred as a single band in normal and hyperplastic mammary tissue, as well as in tumors, and was thus likely to be the inactivated, unphosphorylated form (Gu et al, 1992;Planas-Silva et al, 1997). Cdk2b, on the other hand, was present mainly as the phosphorylated, activated, faster-migrating form (Gu et al, 1992;Planas-Silva et al, 1997) in c-myc and tgfa/c-myc tumors, but it occurred mainly as the inactivated, unphosphorylated slower-migrating band in normal and hyperplastic mammary tissues ( Figure 5).…”
Section: Expression Of Cdk4 Cyclin D3 and Cdk2mentioning
confidence: 99%
“…Regulation of the cyclin E-CDK2 catalytic activity occurs at least through two mechanisms: activation of CDK2 activity by phosphorylation at position Thr-160 (Gu et al, 1992;Morgan, 1995) and modulation of the stoichiometry of p21 Waf1 and p27 Kip1 bound to the complex (La Baer et al, 1997;Zhang et al, 1994). To dissect which of these regulatory mechanisms could be hampered in N1186-94 cells, we analysed both the phosphorylation status of CDK2 and the amount of inhibitors bound to cyclin E.…”
Section: Antiproliferative Signals Do Not Modulate Cyclin E-cdk2 Actimentioning
confidence: 99%